2012
DOI: 10.1111/j.1552-6909.2012.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Neighborhood Environment, Racial Discrimination, Psychological Distress, and Preterm Birth in African American Women

Abstract: Objectives To (a) examine the relationships among objective and perceived indicators of neighborhood environment, racial discrimination, psychological distress, and gestational age at birth; (b) determine if neighborhood environment and racial discrimination predicted psychological distress; (c) determine if neighborhood environment, racial discrimination, and psychological distress predicted preterm birth; and (d) determine if psychological distress mediated the effects of neighborhood environment and racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(158 citation statements)
references
References 40 publications
8
149
0
Order By: Relevance
“…14, 22 Race was considered because previous research has shown that reproductive hormone metabolism and perceived stress vary by race. 23, 24 At the end of the follow-up period, total percent body fat was measured using duel energy X-ray absorptiometry scans.…”
Section: Methodsmentioning
confidence: 99%
“…14, 22 Race was considered because previous research has shown that reproductive hormone metabolism and perceived stress vary by race. 23, 24 At the end of the follow-up period, total percent body fat was measured using duel energy X-ray absorptiometry scans.…”
Section: Methodsmentioning
confidence: 99%
“…Second, in a smaller but racially homogeneous study of 72 AA women, Giurgescu et al also reported no statistically significant association between perceptions of neighborhood social disorder or crime and PTD rates. 8 While these two studies suggest that perceptions of residential environment may have no influence on PTD among AA women, neither study examined effect modification by sociodemographic characteristics, such as educational attainment.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 Two studies with data on AAwomen have examined the impact of perceptions of the residential environment on PTD rates, and found associations that were non-significant (though in the expected direction). 7,8 First, in a cohort of 1898 pregnant AA and White women, Dole and colleagues reported a 40 % increase in PTD rates for White women who perceived their neighborhoods as unsafe, compared to those who perceived their neighborhood as safe. 7 However, when their analyses were restricted to AA women, there was no increase in PTD rates comparing women who reported unsafe versus safe neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of concurrent validity has had acceptable correlations ranging from 0.52–0.80 (Dupuy, 1984). The PGWBI has been used with good reliability with pregnant and postpartum women, including African American women (Giurgescu, Zenk, Dancy, Park, Dieber, & Block, 2012; Giurgescu et al, 2013). In the current study Cronbach’s alpha for the PGWBI was 0.94.…”
Section: Study Measuresmentioning
confidence: 99%